Construction of critical interculturality in a handicraft cooperative of rarámuri and mestizo women - Ruiz Salazar, Grissel Alejandra; Martínez Corona, Guadalupe Beatriz; Zapata Martelo, Emma; Pérez Hernández, Luz María; Arras Vota, Ana María de Guadalupe; Garza Bueno, Laura Elena (Agricultura, Sociedad y Desarrollo, 2022)
Due to the historical coloniality in inter-ethnic relationships between the (dominant) Mestizo population and the (subaltern), Rarámuri population in Chihuahua, Mexico, it was of interest to examine the organizational experience of a handicraft cooperative made up of 21 women from the Rarámuri and Mestizo-Western cultures in the city of Chihuahua from the standpoint of critical interculturality (as opposed to the simple recognition of multicultural presence). The objective was to identify the practice of elements of critical interculturality or expressions of coloniality in the social relationships of its members. The study employed a qualitative research approach, including first-hand observation and in-depth interviews. It identified components of the practice of critical interculturality in inter-ethnic, intra-gender and labor relationships in the organizational processes of the cooperative, for example: knowledge exchange, horizontal decision-making, mutual recognition, and capacity strengthening. It also found the presence of colonizing elements associated with market mechanisms for handicraft products and norms foreign to the Rarámuri culture. The study shows the democratizing potential of the practice of critical interculturality in sorority and exchange of cultural elements, which do not threaten the preservation of the ethnic-cultural identities of the participants.